Answer:
x = -9
y = -3
Step-by-step explanation:
We can first multiply the 2nd equation by -6, so we have:
[tex]-6*[-0.8x+0.4y=6]\\=4.8x-2.4y=-36[/tex]
Now, we add up this equation to the 1st equation given to eliminate y and solve for x. Shown below:
[tex]1.2x+2.4y=-18\\4.8x-2.4y=-36\\---------\\6x=-54\\x=-9[/tex]
So, we have the value of x to be -9
Now, we substitute this value in 1st equation and solve for y:
[tex]1.2x+2.4y=-18\\1.2(-9)+2.4y=-18\\-10.8+2.4y=-18\\2.4y=-7.2\\y=-3[/tex]
The value of y is -3
So,
x = -9
y = -3